Percepatan Pembangunan Ekonomi Daerah Tertinggal (Kabupaten Pesisir Barat) - Lies Maria Hamzah; Erlin Agustin (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
This study aims to determine strategies and policies to accelerate the development of the West Coast District which is one of the underdeveloped areas in Indonesia. The SWOT analysis tool is one of the tools that can be used to develop a strategy through three stages: input, incorporation, decision. The analytical tools used in this study are the IFE (Internal Factor Evaluation) matrix, the EFE (External Factor Evaluation) matrix, and the Strength-Weakness-Opportunity-Threats (SWOT) matrix. The result of the research shows that the development strategy of underdeveloped areas in Pesisir Barat Regency is prioritized by using information technology, including to support tourism development in Pesisir Barat Regency.